2009
DOI: 10.1099/vir.0.008649-0
|View full text |Cite
|
Sign up to set email alerts
|

A multipartite single-stranded negative-sense RNA virus is the putative agent of fig mosaic disease

Abstract: Several dsRNA bands (approx. 0.6-7 kbp in size) were recovered from tissues of mosaicdiseased fig seedlings which contained the enveloped round structures known as double membrane bodies (DMBs). BLAST analysis of a 4353 and a 1120 nt sequence from the two largest RNA segments showed homology with the polymerase and the putative glycoprotein precursor genes of negative-sense single-stranded RNA viruses of the family Bunyaviridae. Negative-and positive-sense riboprobes designed from both RNA segments hybridized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 25 publications
5
103
0
1
Order By: Relevance
“…Comparison of the nucleotides and predicted amino acid sequence of all RNA segments of Emaravirus-like viruses with their homologue showed that RNA1 is the most conserved segments among all others analyzed, for which that of FMV, EMARaV, RLBV, RRV and RYRV revealed the presence of five highly conserved regions denoted as motifs (A-E) in the RdRp gene, similarly to what has been previously reported with FMV and EMARaV by Elbeaino et al, (2009aElbeaino et al, ( , 2009b. Computer-assisted analysis showed that among all five analyzed regions, the pre-motif A, motifs A and C were the most conserved ones (data not shown) (Fig.…”
Section: Design Of Oligonucleotide Degenerate Primers For Emaravirus-supporting
confidence: 79%
See 4 more Smart Citations
“…Comparison of the nucleotides and predicted amino acid sequence of all RNA segments of Emaravirus-like viruses with their homologue showed that RNA1 is the most conserved segments among all others analyzed, for which that of FMV, EMARaV, RLBV, RRV and RYRV revealed the presence of five highly conserved regions denoted as motifs (A-E) in the RdRp gene, similarly to what has been previously reported with FMV and EMARaV by Elbeaino et al, (2009aElbeaino et al, ( , 2009b. Computer-assisted analysis showed that among all five analyzed regions, the pre-motif A, motifs A and C were the most conserved ones (data not shown) (Fig.…”
Section: Design Of Oligonucleotide Degenerate Primers For Emaravirus-supporting
confidence: 79%
“…Leaf vein tissues (10 g) from infected plant materials were used to recover dsRNAs by phenol/chloroform extraction and chromatography through cellulose CF-11 column in the presence of 17% ethanol (Elbeaino et al, 2009a). Extracts were followed by selective digestion by DNase and RNase (Dodds, 1993).…”
Section: Extraction Of Total Nucleic Acid (Tna) and Double-stranded Rmentioning
confidence: 99%
See 3 more Smart Citations